Contribution to the study of the Afrotropical Pyraustinae Meyrick, 1890 (Lepidoptera, Crambidae): Taxonomic and distributional updates on five species with new country records - Michael Seizmair; Alrabea Ishag; Hathal Al Dhafer (Biodiversity Data Journal)
The Pyraustinae Meyrick, 1890 form the fifth most diverse subfamily in the Pyraloidea, comprising 1270 described species distributed over 173 genera. For the Afrotropical zone, a total of 160 species have become known to date. Faunistic studies on the subfamily for the Afrotropical zone have been to date regionally confined on the southern parts of Africa, including South Africa, the Mascarene and Malagasy islands. The other parts of sub-Saharan Africa have remained understudied. This results in still unexplored distribution patterns of the Afrotropical Pyraustinae. The Afrotropical zone reaches its northern boundaries in the southern parts of the Arabian Peninsula which include the southern part of Oman (Province Dhofar), Yemen and the south-western parts of Saudi Arabia. For the Pyraustinae, the Arabian Peninsula has been little explored to date. No more than 20 species distributed over 13 genera have become known.Taxonomic and distributional updates are presented on five species of the Pyraustinae (Lepidoptera, Crambidae), based on material from East and Central Africa and from the tropical parts of the Arabian Peninsula. Ecpyrrhorrhoe diatoma (Hampson, 1913) and Psammotis haematidea (Hampson, 1913) are re-described, with the male and female genitalia described and figured for the first time. A new combination Paschiodes postmediofusalis (Seizmair, 2022) comb. n. from Pyrausta Hübner, 1825 is introduced, with the diagnostic characters differentiating the species from the other species of the Afrotropical genus Paschiodes Hampson, 1913 being listed. Psammotis haematidea (Hampson, 1913), Ecpyrrhorrhoe diatoma (Hampson, 1913) and Euclasta warreni Distant, 1892 are reported as new to the Arabian Peninsula. Psammotis haematidea (Hampson, 1913) is furthermore reported as new to Kenya and Cameroon. Paschiodes postmediofusalis (Seizmair, 2022) comb. n. and Euclasta varii Popescu-Gori & Constantinescu, 1973 are reported as new to Saudi Arabia. For each of the taxa presented, external and internal diagnostic characters are listed and illustrated.